Prospect Theory as Efficient Perceptual Distortion - Woodford, Michael (American Economic Review, 2012)
The paper proposes a theory of efficient perceptual distortions, in which the statistical relation between subjective perceptions and the objective state minimizes the error of the state estimate, subject to a constraint on information processing capacity. The theory is shown to account for observed limits to the accuracy of visual perception, and then postulated to apply to perception of options in economic choice situations as well. When applied to choice between lotteries, it implies reference-dependent valuations, and predicts both risk-aversion with respect to gains and risk-seeking with respect to losses, as in the prospect theory of Kahneman and Tversky (1979).